1999
DOI: 10.1016/s0029-7844(99)00389-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of fetuses diagnosed with atrioventricular septal defect

Abstract: Prenatal diagnosis of atrioventricular septal defect was associated with a 58% risk of aneuploidy (mainly trisomy 21). Down syndrome fetuses with this cardiac anomaly appeared to have a better survival rate than fetuses with normal karyotypes. Our sample did not have enough power to show a statistically significant difference. When an isolated atrioventricular septal defect was diagnosed prenatally, the odds of trisomy 21 were significantly higher than when other associated cardiac lesions were diagnosed. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…1,4,9 Following a diagnosis of AVSD, parents are usually offered an invasive test for fetal karyotyping. 1,7,9,13 The overall frequency of aneuploidy detected prenatally in our relatively small cohort is only 31%.…”
Section: Abnormal Karyotypementioning
confidence: 99%
See 2 more Smart Citations
“…1,4,9 Following a diagnosis of AVSD, parents are usually offered an invasive test for fetal karyotyping. 1,7,9,13 The overall frequency of aneuploidy detected prenatally in our relatively small cohort is only 31%.…”
Section: Abnormal Karyotypementioning
confidence: 99%
“…[1][2][3][4][5] The identification of this lesion prenatally has important implications for the fetus due to the high rate of associated extracardiac malformations, such as Down syndrome or the syndromes of disturbed atrial situs. 2,4,6,7 The spectrum of AVSD in fetal life is different from that diagnosed postnatally due to the possibility of termination and in utero fetal demise. Up to 45% of those diagnosed in utero may have associated heterotaxy syndromes, particularly left atrial isomerism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaoui et al [11] found chromosomal abnormalities in 22.7% (46/203) of the fetuses with CHD including trisomy 18 (n Z 15), trisomy 21 (n Z 13), trisomy 13 (n Z 5), 45,X (n Z 5), triploidy (n Z 2), and other rearrangements (n Z 6). Prenatal diagnosis of an atrioventricular septal defect has been associated with a high risk of aneuploidy up to 49.1e57.9% [12,13]. Delisle et al [12] reported aneuploidy in 57.9% (22/ 38) of the fetuses with an atrioventricular septal defect including trisomy 21 (n Z 19), trisomy 18 (n Z 1), trisomy 13 (n Z 1), and mosaic trisomy 19q (n Z 1).…”
mentioning
confidence: 99%
“…Prenatal diagnosis of an atrioventricular septal defect has been associated with a high risk of aneuploidy up to 49.1e57.9% [12,13]. Delisle et al [12] reported aneuploidy in 57.9% (22/ 38) of the fetuses with an atrioventricular septal defect including trisomy 21 (n Z 19), trisomy 18 (n Z 1), trisomy 13 (n Z 1), and mosaic trisomy 19q (n Z 1). Huggon et al [13] reported aneuploidy in 49.1% (107/218) of the fetuses with an atrioventricular septal defect including trisomy 21 (n Z 86), trisomy 18 (n Z 13), trisomy 13 (n Z 4), and other rearrangements (n Z 4).…”
mentioning
confidence: 99%